1985
DOI: 10.1021/jf00066a032
|View full text |Cite
|
Sign up to set email alerts
|

Increased furocoumarin content of celery during storage

Abstract: Diseased celery infected with the fungus Sclerotinia sclerotiorum had greatly increased levels of three phytoalexin furocoumarins, namely psoralen, 5-MOP, and 8-MOP, which are responsible for skin photosensitivity. Storage of freshly harvested celery at 4 °C resulted in clear signs of fungal infection, from latent fungus, appearing within 23-29 days, with concomitant increases in total furocoumarin levels from 1.84 ppm (wet weight) to 43.82 ppm and with occasional samples as high as 95.52 ppm. Psoralen, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 7 publications
2
53
0
Order By: Relevance
“…In some plants, seed germination occurs only after psoralens have been leached out from the seeds into the soil. The released psoralens inhibit germination of surrounding seeds (Baskin et al 1967;Zobel and Brown 1988;Chaudhary et al 1985;Zangerl 1990;Nguyen et al 1997). In this context, present study will explain and elucidate the effects of gamma rays on the production of psoralen, growth and development.…”
Section: Introductionmentioning
confidence: 90%
“…In some plants, seed germination occurs only after psoralens have been leached out from the seeds into the soil. The released psoralens inhibit germination of surrounding seeds (Baskin et al 1967;Zobel and Brown 1988;Chaudhary et al 1985;Zangerl 1990;Nguyen et al 1997). In this context, present study will explain and elucidate the effects of gamma rays on the production of psoralen, growth and development.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Chaudhary et al (1985) considered the linear furanocoumarins, psoralen (6), xanthotoxin and bergapten (7) to be phytoalexins of celery (Apium graveolens) by reporting that diseased celery infected with the fungus Sclerotinia sclerotiorum had greatly increased the levels of these compounds that are normally found in healthy celery (Beier and Oertli, 1983;Chaudhary et al, 1985;Ashwood-Smith et al, 1986;Trumble et al, 1990). Similarly, Al-Barwani (2002) in her survey of phytoalexins in a number of umbelliferous species found that the majority of the species studied produce high levels of furanocoumarins as a result of induction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hyphenated techniques such as LC-MS provides great information about the content and nature of constituents of complex natural matrices prior to fractioning and carrying out biological assays. Moreover, MS presents a great advantage not only in its ability to measure accurate ion masses but also in its use in structure elucidation (Chaudhary et al, 1985;Dugo et al, Waksmundzka-Hajnos & Sherma, 2011).…”
Section: Hyphenated Hplc Techniquesmentioning
confidence: 99%